Planning strategies in the audit (Revista Torreón Universitario, 2022)
The Planning of the Audit guarantees the design of a strategy adapted to the conditions of each entity based on the information gathered in the Previous Exploration stage, in this process all the Audit work is organized, the people involved, the tasks to be performed For each of the performers, the necessary resources, the objectives, programs to be applied among others, it is time to plan to guarantee success in the execution of the same.The audit procedures are not standardized and those that are used are selected because they have particular significance with the work objectives. When the audit is planned properly, the general strategy for the examination is developed. It is essential that the auditor is thoroughly familiar with the entity. Adequate planning includes the auditor's acquisition of an understanding of the operational nature of the business, its organization, location of its facilities, sales, productions, services provided, its financial structure, purchase and sale operations and many other issues that may be significant in which you will audit. It must also know in advance the degree of confidence that can be had in the internal control, conditions that may require an extension of the audit tests, and in particular the interests of the highest Management. Often the level of knowledge acquired by the auditor is lower than that of the administration, but it must be sufficient to allow the auditor to plan and carry out the examination in accordance with generally accepted auditing standards.
Keywords: Audit procedures; audit planning; audit strategies; audit tests; work programs